Perancangan Alat Cetak Pelet Ayam Portabel Guna Mengurangi Biaya Pembelian Pakan (Studi KAsus: Peternakan Pak Musraji) - Prayoga, M Danyago; Herlina, Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The design of a pellet molding tool is a solution to reduce the burden of broiler feed production and reduce the cost of purchasing feed. In this design I innovated a portable chicken pellet molding tool that can be used without having to have an electrical outlet nearby. The working principle of this pellet molding tool is sequentially when the electric motor is turned on, the feed raw material mixture is fed into the funnel, the engine power will be distributed to the axle screw via a v-belt transmission by moving the roller press which functions to stir the pellet raw material. Pellet raw materials that have been thoroughly mixed will fall down to the end of the output funnel. The pellet raw material mixture will come out through the hole screen to form pellets. The results of the trial of a chicken pellet press with a 5Kw motor can produce 100 kg/hour of chicken pellets and a cost efficiency of IDR 25,920,000/month is also obtained.